Preface. Religion and education - Fylypovyč, Ljudmyla Oleksandrivna (Ukrai͏̈ns'ke relihijeznavstvo, 2014)
Religion and education are a topic that has emerged relatively recently in the Ukrainian information, research, and educational space. The relationship between religion and education meditated before, but usually in a negative sense. New circumstances also dictate new approaches to the stated topic. Polyphony of thoughts holds in itself and explicit criticism of any possibility of coexistence of religion and education, vulgarly linking religion with obscurantism, which can not bear any enlightenment, blurring the brain of a person. Such pre-historic estimates of religion are less and less popular in society, which in those years has "opened" a religion (as opposed to the present and still existing perception of it as a fantastic reflection in the heads of people of those external forces that prevail over them) as a spiritually rich reality as something that fills the meaning of human existence, defines the vocation of the person asserting it in the world, in society, in their own lives.